(untitled) (GYMNASIUM, 2009)
In ontogenesis, the neuromotor equipment and the sensory proprioceptive apparatus are progressively “processed”, and both the processes of the primary knowledge – sensation, perception, representation, but also those of the evolved ones – language memory rational thinking develop themselves through movement. These processes are differently sedimented, according to the sensory-motor fluxes, from the frame of every stimulus – response relationship of a certain physical action. The more intense these are, the more balanced the corporal scheme is, and assures the objectivization of certain important data linked to the real possibilities of execution of certain motor structures.